Economic vulnerability of timber resources to forest fires. - Rodríguez y Silva, Francisco; Molina, Juan Ramón; González-Cabán, Armando; Machuca, Miguel Ángel Herrera; y Silva, Francisco Rodríguez; Molina, Juan Ramón; González-Cabán, Armando; Machuca, Miguel Ángel Herrera (Journal of environmental management, 2012)
The temporal-spatial planning of activities for a territorial fire management program requires knowing the value of forest ecosystems. In this paper we extend to and apply the economic valuation principle to the concept of economic vulnerability and present a methodology for the economic valuation of the forest production ecosystems. The forest vulnerability is analyzed from criteria intrinsically associated to the forest characterization, and to the potential behavior of surface fires. Integrating a mapping process of fire potential and analytical valuation algorithms facilitates the implementation of fire prevention planning. The availability of cartography of economic vulnerability of the forest ecosystems is fundamental for budget optimization, and to help in the decision making process.
Keywords: Conservation of Natural Resources; Conservation of Natural Resources: economics; Decision Making; Economic valuation; Ecosystem; Fire economic losses; Fire prevention planning; Fires; Timber valuation; Trees